Updated upper limit of normal for serum alanine aminotransferase value in Vietnamese population. Issue 1 (25th May 2022) - Huong, Nguyen Thi Cam; Karimzadeh, Sedighe; Thanh, Nguyen Thi; Thuan, Tieu Minh; Sabbah, Ghada Mohamed; Ismaeil, Khaled; An, Dang Nguyen Trung; Huong, Lai To; Huy, Nguyen Tien; Thi Le Hoa, Pham
Abstract : Background: Alanine aminotransferase (ALT) is a marker of hepatic damage and its range can be affected by viral hepatitis, alcoholic hepatitis and non-alcoholic fatty liver diseases. We aimed to study the factors associated with higher ALT level and update the upper limit of normal (ULN) in the Vietnamese population. Methods: This cross-sectional study enrolled 8383 adults, aged 18 years and older who visited the Medical Center at Ho Chi Minh City for a health check-up. Following the exclusion criteria, 6677 subjects were included in the analysis. Results: Age ≤40 years, male gender, body mass index >23 kg/m 2, diastolic blood pressure >85 mm Hg, cholesterol >5.2 mmol/L, triglyceride >1.7 mmol/L, positivity, anti-hepatitis C virus positivity and fatty liver (p<0.05) were associated with higher ALT level (>40 U/L). Without considering age and gender, healthy group is defined after exclusion of participants with one of the mentioned contributing factors. The median ALT level in the healthy group was 18 in men and 13 in women. The ULN at the 95th percentile of the healthy group was 40 U/L in men and 28 U/L in women. Conclusion: The ULN for ALT in healthy women was lower than in healthy men. Updated ULN for ALT level can promote the identification of unhealthy subjects. More studies that involve ethnicity and lifestyle factors are needed to confirm the new ULN in the Vietnamese population.